Efektivitas Penggunaan Teknologi dalam Pelaksanaan Bimbingan Penyuluhan Islam - Yanto Yanto; Abdul Hamid Bashori (Berkala Ilmiah Pendidikan, 2024)
The research aims to explain and describe the effectiveness of technology utilization in the implementation of Islamic counseling and guidance. The research method employed is qualitative through literature review, with data collection techniques using documentary studies. Data processing involves reduction, data presentation, and inference. The research results indicate that Islamic counseling and guidance provide assistance in solving problems based on the values of Islamic teachings. The effectiveness of technology, such as cyberextension, YouTube, Instagram, radio, and websites, is demonstrated to be more effective and efficient due to their ease of creation and accessibility anytime, anywhere. The impact of using these technological platforms is the ease of accessing, creating, and learning from the provided content or information. The difference between conventional and technological Islamic counseling and guidance lies in face-to-face and non-face-to-face implementations, with success depending on the counselor or technology user, among other factors. In conclusion, the use of technology in Islamic counseling and guidance activities is more effective when conducted in a classical manner.